Foreign Direct Investment and Regional Attractiveness in Southeastern European countries - Aikaterini Kokkinou; Yannis Psycharis (European Regional Science Association (ERSA), 2005)
The aim of this paper is to analyse the relationship between the inward Foreign Direct Investment in South-eastern European countries in relation with the factors which determine the ability of a country to attract foreign investment capital. The paper begins with the definition of the main terms related with Foreign Direct Investment and literature review related with the factors which determine the regional allocation of the FDI flows. Specifically, the article focuses on the definition of the Foreign Direct Investment flows, regional attractiveness, location of FDI, as well as the factors which affect the location of FDI activities within and across countries and regions. Then, the article presents a comparative analysis of the relative position of the South-eastern European countries, as far as FDI is concerned. Moreover, the paper attempts, through a model specification and results analysis to estimate the relationship between FDI and a selection of potential determining factors. The analysis is made for thirteen South-eastern European countries covering a period of twelve years. The paper is completed with reference to prospects regarding the implementation and planning of an effective FDI attraction policy aiming at economic development and cohesion.
Keywords: 330